2016
DOI: 10.1371/journal.pone.0161267
|View full text |Cite
|
Sign up to set email alerts
|

Computational Model for Tumor Oxygenation Applied to Clinical Data on Breast Tumor Hemoglobin Concentrations Suggests Vascular Dilatation and Compression

Abstract: We present a computational model for trans-vascular oxygen transport in synthetic tumor and host tissue blood vessel networks, aiming at qualitatively explaining published data of optical mammography, which were obtained from 87 breast cancer patients. The data generally show average hemoglobin concentration to be higher in tumors versus host tissue whereas average oxy-to total hemoglobin concentration (vascular segment RBC-volume-weighted blood oxygenation) can be above or below normal. Starting from a synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(85 citation statements)
references
References 89 publications
(137 reference statements)
3
82
0
Order By: Relevance
“…In [15] we showed that the equation for the vascular oxygen distribution together with 104 the diffusion equation for the tissue form a complicated nonlinear system of equations 105 with the partial pressure values of oxygen as unknowns. For the longitudinal transport a 106 bisection search is used to gather the partial oxygen pressure values within each vessel.…”
Section: Finite Elements Methods 103mentioning
confidence: 99%
See 1 more Smart Citation
“…In [15] we showed that the equation for the vascular oxygen distribution together with 104 the diffusion equation for the tissue form a complicated nonlinear system of equations 105 with the partial pressure values of oxygen as unknowns. For the longitudinal transport a 106 bisection search is used to gather the partial oxygen pressure values within each vessel.…”
Section: Finite Elements Methods 103mentioning
confidence: 99%
“…Secondly, an elaborated model of blood and tissue oxygenation was developed [15]. 181 Similarly to 'submitIff', 'submitDetailedO2' needs a parameter set, a tumor simulation 182 and a specified time point as input.…”
mentioning
confidence: 99%
“…The authors investigated the structural adaptation of tumour vasculature and its pruning in response to haemodynamic and metabolic stimuli as well as spatial patterns and frequency distributions of both oxygen and VEGF concentrations around vascular networks of distinct topologies (figure 2c). Welter and co-workers [87,97] modelled the complex hierarchical tree-like vascular structures via a hybrid model combining a discrete triangular grid-based vascular network and a continuous description of a homogeneous medium representing host or tumour cells. The authors investigated the relation between the morphology of tumour vasculature and the intra-and extravascular transport characteristics of blood flow, oxygen distribution, interstitial fluid pressure and drug delivery efficiency.…”
Section: Mathematical Models Of Vascularized Tumours and Angiogenesismentioning
confidence: 99%
“…Second, the position of the capillaries within the volume is optimized towards a homogeneous capillary volume density using a hierarchical iteration scheme. For the scope of this paper, we consider only a root node configuration (RC) where one artery is opposite to one vein on the same axis (figure 2, compare also RC5 in figure 4 75 of [24]) and a single hierarchical iteration. Since the construction algorithm in the Tumorcode fixes the radii of all capillaries ( 2.5 µm in presented case) and determines the radii of all intermittent vessels between root nodes and capillaries by Murray's law, all radii at the intersections fulfill Murray's law by construction.…”
Section: The Artificial Blood Vessel Networkmentioning
confidence: 99%
“…In solid tumors, topological 240 modifications are an essential part of the growth procedure and therefore considered in our simulation framework [21]. In [24], we simulated the oxygen distribution in breast carcinoma and found that an additional vessel dilation is required to obtain oxygen distributions in agreement with the clinical measurements. We conjectured that the adaptation algorithm could possibly 245 provide a physiological mechanism for this vessel dilation.…”
Section: Application To Cancerous Networkmentioning
confidence: 99%